Noise and Vibration Risk Assessment for the Operators of Crawler Loaders - CARLETTI, Eleonora; PEDRIELLI, Francesca (Archives of Acoustics, 2019)
During work, earth-moving machines generate significant levels of noise and vibration that can be harmful for the operators; therefore the analysis of the noise and vibration conditions at the driving position is of great importance for the risk assessment. Compact loaders have become a pressing challengeas they are extremely hazardous referring to noise and vibration emissions, especially in their crawler version where further relevant noise and vibration are generated by the hard contact between track belt and ground.This paper reports the results of investigations carried out on three crawler compact loaders in different operating conditions. The main purpose was to investigate the noise and vibration values transmitted to the operators in some working conditions and use these data to obtain reliable estimates of the exposure to noise, to whole-body and to hand-arm transmitted vibrations, as well as to evaluate the related risk levels. Vibration signals transmitted to the operator were acquired on the seat and the machine control lever in accordance with the procedures specified in ISO 2631-1 and ISO 5349-1. At the same time, noise signals were acquired at the operator’s ear following the procedure reported in ISO 11201. Vibration signals were also acquired on the cabin floor with the main purpose to evaluate the effectiveness of the machine seats in reducing the vibration transmission. Finally, the noise and vibration exposure risks were evaluated on the basis of the health and safety requirements established in 2003/10/EC and 2002/44/EC Directives.